HUBUNGAN REPETITIF DAN GETARAN DENGAN TERJADINYA KELUHAN CARPAL TUNNEL SYNDROM PADA PEKERJA KONSTRUKSI PT PRIMA ABADI JAYA DI MEDAN TAHUN 2025 - Hasian, Muhammad Tsawaby; siregar, ripai; siddiq, muhraza (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
Carpal Tunnel Syndrome (CTS) is a condition caused by pressure on the median nerve in the wrist which can cause symptoms such as tingling, radiating pain, numbness, muscle weakness, stiffness, and possibly muscle wasting. In Denpasar, in 2021, workers were found to have a preval_ence of carpal tunnel syndrome of 79.2%. This study aimed to determine the factors that influence the occurrence of Carpal Tunnel Syndrome complaints among construction workers in PT PAJ Medan. The type of research was Quantitative with Observational methods with a Cross-Sectional approach. The total population is 40 workers with a sample of 40 respondents. The results of the analysis shown that there is a relationship between repetitive movements and the occurrence of CTS complaints in tailor workers in Deli Tua Village with a value of p = 0.005 (p < 0.05), there is a relationship between vibration and the occurrence of CTS complaints with a value of p = 0.002 (p < 0.05). The suggestion of this study conducted that to make a rest schedule while working and pay more attention to the complexity of making patterns so that they can reduce repetitive movements so that the risk of Carpal Tunnel Syndrome decreases, take advantage of their rest hours by not increasing their working hours at night, stretch (such as relaxing the back muscles, neck, shoulders, hands and feet for 5-10 minutes).